2020
DOI: 10.3389/fped.2020.601892
|View full text |Cite
|
Sign up to set email alerts
|

The BAL-Score Almost Perfectly Predicts Testicular Torsion in Children: A Two-Center Cohort Study

Abstract: Introduction: Testicular torsion (TT) is a common emergency that warrants immediate exploration to prevent infertility or testicular loss. To improve diagnostic reliability, various scoring systems have been published. The aim of this study was to evaluate and validate different testicular torsion scores in a large cohort of children with acute scrotum.Methods: Retrospective analysis of all male children that were admitted for acute scrotum at the Pediatric Surgery Department of the Altonaer Kinderkrankenhaus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
9
0
2
Order By: Relevance
“…In addition, NLR, PLR, MER and RDW were found to be statistically significantly higher in all scrotal pathologies compared to the control group. In current studies, CBC‐obtained inflammatory markers were found to be statistically higher in ASPs than the control group but scrotal pathologies and particularly TT and EO could not be distinguished according to these markers (Arikan et al, 2021; Klinke et al, 2020; Ozbir et al, 2020; Patel et al, 2013; Rachidi et al, 2014). In the aforementioned studies, we think that this may be primarily associated with the systemic inflammatory response and inflammatory markers like PLR and RDW that increase in vascular pathologies in studies using varicocele patients as the control group is greater compared to our healthy control group and the smaller number of cases.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, NLR, PLR, MER and RDW were found to be statistically significantly higher in all scrotal pathologies compared to the control group. In current studies, CBC‐obtained inflammatory markers were found to be statistically higher in ASPs than the control group but scrotal pathologies and particularly TT and EO could not be distinguished according to these markers (Arikan et al, 2021; Klinke et al, 2020; Ozbir et al, 2020; Patel et al, 2013; Rachidi et al, 2014). In the aforementioned studies, we think that this may be primarily associated with the systemic inflammatory response and inflammatory markers like PLR and RDW that increase in vascular pathologies in studies using varicocele patients as the control group is greater compared to our healthy control group and the smaller number of cases.…”
Section: Discussionmentioning
confidence: 63%
“…Complete blood count (CBC) and biochemical parameters obtained from the peripheral blood had to be within the 1‐week period before the diagnosis and had to be obtained during the preoperative period from surgical candidates (Shah et al, 2016). For blood sampling and reference ranges, local laboratory techniques and parameters complying with current literature data and methods were taken into consideration (Klinke et al, 2020; Patel et al, 2013). NLR, PLR and MER values were obtained from the proportion of absolute neutrophils/absolute lymphocytes, absolute platelets/absolute lymphocytes and absolute monocytes/absolute eosinophils respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, when classical symptoms appear inconsistently, pain is intermittent and non-specific symptoms occur, diagnosis and treatment may be delayed [ 11 ]. Two common scores for evaluating the probability of testicular torsion—TWIST (testicular workup for ischemia and suspected torsion) and BAL (Boettcher alert score)—have shown high sensitivity and specificity for predicting testicular torsion [ 11 , 16 , 17 , 18 ]. However, they rely on classical clinical symptoms (pain, nausea/emesis, displacement of the testicle, abnormal cremasteric reflex, swelling and hardened testicle), the majority of which were not present in our case.…”
Section: Discussionmentioning
confidence: 99%
“…3 Evaluated clinical scores for assessing the probability of testicular torsions, such as the Testicular Workup for Ischemia and Suspected Torsion (TWIST) score and the Boettcher Alert (BAL) score, have proven excellent sensitivity and specificity. 4,5 Doppler ultrasonography of the scrotum can also help in determining the proper diagnosis.…”
Section: Introductionmentioning
confidence: 99%